Self-control and aggressiveness as mediating factors between motivational orientations and sportspersonship - de Palo, V.; Monacis, L.; Carlucci, L.; Tanucci, G.; Sinatra, M. (Journal of Human Sport & Exercise, 2019)
In light of the increasing propensity toward unsportsmanlike behaviours that have caused the failure of the notion of fair play, this research tested a causal model of theoretically-predicted antecedents of sportspersonship, in which the two trait-related personality factors, self-control and aggressiveness, mediated the relationship between motivational orientations and sportspersonship. After examining the five-factor structure of the Multidimensional Sportspersonship Orientation Scale in a first sample of Italian athletes (n = 371, Mage = 26.57), the resulting 20-item four-factor model proved to be satisfactory and reliable. In a second sample (n = 814, Mage = 25.96) the proposed empirically-based model confirmed the important role played by self-control in mediating the relationship between ego orientation, aggressiveness, and sportspersonship. In terms of practical implications, the findings provide a more comprehensive conceptualization of the factors that differentiate the inter- and intra-individual characteristics in sportspersonship, thus allowing practitioners to develop effective intervention programs addressed to athletes.